Commentary: sex difference differences? A reply to Constantino. Issue 1 (December 2016) - Messinger, Daniel; Young, Gregory; Webb, Sara; Ozonoff, Sally; Bryson, Susan; Carter, Alice; Carver, Leslie; Charman, Tony; Chawarska, Katarzyna; Curtin, Suzanne; Dobkins, Karen; Hertz-Picciotto, Irva; et al.
Abstract Messinger et al. found a 3.18 odds ratio of male to female ASD recurrence in 1241 prospectively followed high-risk (HR) siblings. Among high-risk siblings (with and without ASD), as well as among 583 low-risk controls, girls exhibited higher performance on the Mullen Scales of Early Learning, as well as lower restricted and repetitive behavior severity scores on the Autism Diagnostic Observation Schedule (ADOS) than boys. That is, female-favoring sex differences in developmental performance and autism traits were evident among low-risk and non-ASD high-risk children, as well as those with ASD. Constantino (Mol Autism) suggests that sex differences in categorical ASD outcomes in Messinger et al. should be understood as a female protective effect. We are receptive to Constantino's (Mol Autism) suggestion, and propose that quantitative sex differences in autism-related features are keys to understanding this female protective effect.